(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the electrophysiological characteristics of nerve cells from a biophysical standpoint. Nerve cells, or neurons, communicate through electrical signals generated by ion movements across their membranes. The study focuses on the fundamental mechanisms underlying action potential generation, propagation, and synaptic transmission. Key concepts such as membrane potential, ion channel function, and the role of voltage-gated ion channels are examined in detail. The article further discusses the application of biophysical techniques like patch-clamp recording and voltage-sensitive dyes in investigating neuronal electrical behavior. Understanding these electrophysiological properties is crucial for comprehending nervous system function and addressing neurological disorders. The insights gained from biophysical analyses contribute to the development of therapeutic strategies targeting dysfunctional neuronal activity.